2013
DOI: 10.4028/www.scientific.net/amr.743.27
|View full text |Cite
|
Sign up to set email alerts
|

Soil Nailing Optimization Design of Foundation Pit Based on Response Surface of SVM Technology

Abstract: In order to study the soil nail optimization of foundation pit and obtain the global optimal solution, this paper establishes the predictive model of response surface by combining uniform test design(UD) and the support vector machine(SVM) technology. In order to avoid the disadvantages of large amount of calculation and low efficiency in heuristic algorithm, and to gain the optimal model of the explicitly analytical function in gradient algorithm, based on the predictive model of response surface under the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The response surface methodology (RSM)-based design model is used to optimize the soil nailing condition of the foundation pit. 27 The optimized soil geotechnical properties of the pressure meter test are analyzed by Lafifi et al 28 using the combined DOE Taguchi and RSM approach. Benayoun et al 29 have utilized the RSM to identify the influencing factor of wall stability and construction cost in case of soil nailing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response surface methodology (RSM)-based design model is used to optimize the soil nailing condition of the foundation pit. 27 The optimized soil geotechnical properties of the pressure meter test are analyzed by Lafifi et al 28 using the combined DOE Taguchi and RSM approach. Benayoun et al 29 have utilized the RSM to identify the influencing factor of wall stability and construction cost in case of soil nailing.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the Coot optimization algorithm is used. The response surface methodology (RSM)‐based design model is used to optimize the soil nailing condition of the foundation pit 27 . The optimized soil geotechnical properties of the pressure meter test are analyzed by Lafifi et al 28 .…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of geotechnical studies have been reported in the literature on the use of RSM technique of optimization, from which we can cite the precursor work of Sivakumar Babu and Singh (2009) where, to better understand the deformation behavior of the soil nail walls, they carried out numerical experiments and regression models for the maximum lateral deformation and the prediction of the safety factor. Liu et al (2013) proposed a response surface optimization design method for the foundation pit soil nailing, and Algin (2016) used RSM in the multiobjective optimization analysis to present the optimized design solution of a jet grouted raft. An interesting study by Güllü and Fedakar (2017) used RSM in the optimization of material stabilization in terms of their dosage rates.…”
Section: Introductionmentioning
confidence: 99%